EFEKTIVITAS DALAM MEMBENTUK KEBIASAAN MEMBACA PADA SISWA SDN 11 LUBUK KELIAT GUNA MENINGKATKAN LITERASI INFORMASINYA - Agustria, M.Rizki (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2025)
The emergence of the school literacy movement is something that is highly expected by many parties when viewed from the level of interest in reading in Indonesia. The study aims to determine the effectiveness of forming reading habits in students. The research method uses descriptive with the implementation of a qualitative approach at SDN 11 Lubuk Keliat, and the steps taken to obtain research data are observation, interviews and literature studies. The data used in this study are primary data and secondary data. The results showed that the School Literacy Movement was a movement in getting students used to reading which succeeded in increasing students' interest in reading. Students' interest in reading can increase because this program makes students already feel commonplace in reading activities. The increased interest in reading is due to participating in reading non-educational books for 15 minutes before class, students feel that reading is a fun activity and not boring. Students are happy in their reading activities. In addition, the school environment is designed to have a nuance in reading and writing.